2019
DOI: 10.3390/pathogens8040246
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effects of Immunosuppressive Drugs on the Anti-Aspergillus Activity of Human Natural Killer Cells

Abstract: As the prognosis of invasive aspergillosis remains unacceptably poor in patients undergoing hematopoietic stem cell transplantation (HSCT), there is a growing interest in the adoptive transfer of antifungal effector cells, such as Natural Killer (NK) cells. Because immunosuppressive agents are required in most HSCT recipients, knowledge of the impact of these compounds on the antifungal activity of NK cells is a prerequisite for clinical trials. We, therefore, assessed the effect of methylprednisolone (mPRED),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Moreover, patients undergoing solid organ transplantation who presented a higher mean NK cell count suffered less development of invasive fungal disease [127]. Of note, immunosuppressive treatments required in these patients, such as methylprednisolone and cyclosporine A have a negative impact on NK cell function and survival, suggesting that modifications of clinical protocols should be considered for NK cells to maintain activity [128]. Moreover, addition of antifungal agents at therapeutic doses to NK cells did not inhibit the functional activity of NK cells [129].…”
Section: Nk Cells Alone and In Collaboration To Fight Fungal Infectionsmentioning
confidence: 99%
“…Moreover, patients undergoing solid organ transplantation who presented a higher mean NK cell count suffered less development of invasive fungal disease [127]. Of note, immunosuppressive treatments required in these patients, such as methylprednisolone and cyclosporine A have a negative impact on NK cell function and survival, suggesting that modifications of clinical protocols should be considered for NK cells to maintain activity [128]. Moreover, addition of antifungal agents at therapeutic doses to NK cells did not inhibit the functional activity of NK cells [129].…”
Section: Nk Cells Alone and In Collaboration To Fight Fungal Infectionsmentioning
confidence: 99%
“… Gao et al (2019) reported that subcutaneous injection of endothelial colony-forming cells and placenta-derived mesenchymal stromal cells transduced with a BDD-FVIII-expressing lentiviral vector achieved long-term engraftment and FVIII expression for 2 weeks in HA mice treated with cyclosporine A. However, side effects of immunosuppressive drugs have been described ( Dobbels et al, 2008 ; Schmidt et al, 2019 ; Brami et al, 2020 ). Wang et al (2013) implanted hFVIIIBD-MSCs isolated from hFVIIIBD -transgenic mice into HA mice by intravenous injection and achieved a therapeutic effect that lasted for 5 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…When normal flora is traumatically introduced to an area of the body that they do not normally occur in (that is axenic). When there are genetic defects (such as Chronic granulomatous disease), exposure to antimicrobial drugs or immunosuppressive chemicals following poisoning or cancer chemotherapy, exposure to ionizing radiation or as a result of an infectious disease with immunosuppressive activity such as with measles, malaria or HIV disease resulting in the impairment of host defences [5]. Primary pathogens may also cause more severe disease in a host with depressed resistance than would normally occur in an immune sufficient host.…”
Section: Opportunistic Pathogensmentioning
confidence: 99%